Use of Caesalpinia bonducella Seed Shell Waste as Filler for Reinforcement in Epoxy Composites - K. Murugananthan; S. Senthil; P. Senthamaraikannan; R. Kumar (Journal of Natural Fibers)
The chemical, physical, thermal, and morphology analysis of Caesalpinia bonducella seed shell powder (CBSSP) has been conducted for behavior investigation. CBSSP has a high availability of cellulose (61.26 wt.%) from the chemical analysis and also contains minimum contents of hemi cellulose (13.74 wt.%), lignin (12.59 wt.%), wax (0.52 wt.%), ash (8.61 wt.%) and moisture (3.28 wt.%). The X-ray diffraction analysis calculated the crystallinity index as 23.04% and crystalline size as 4.745 nm of CBSSP. CBSSP was probative to surface morphology investigation by Scanning Electron Microscope (SEM) and Atomic Force Microscope (AFM). The thermogravimetric study (TGA) of the CBSSP shows a kinetic energy activation of 66.32 kJ/mol with temperature consistency as high as 225°C, implying the substance could be used as a material filler for thermoplastic resins that perform well at temperatures for processing. Mechanical testing results of CBSSP/Epoxy composite plates revealed that 9 wt.% CBSSP reinforced CBSSP/Epoxy composite plates have improved tensile strength (38.73 MPa), flexural strength (64.41 MPa), and impact strength (4.57 GPa). The results of the specified behavior features of filler could be employed in developing reinforced epoxy composites.